Quality of life in patients with vertebral fractures: validation of the Quality of Life Questionnaire of the European Foundation for Osteoporosis (QUALEFFO). Working Party for Quality of Life of the European Foundation for Osteoporosis. - Lips, P; Cooper, C; Agnusdei, D; Caulin, F; Egger, P; Johnell, O; Kanis, J; Kellingray, S; Leplege, A; Liberman, U; McCloskey, E; Minne, H; et al. (1999)
Vertebral fractures may be minor or lead to pain, decreased physical function, immobility, social isolation and depression, which together contribute to quality of life. A Working Party of the European Foundation for Osteoporosis has developed a specific questionnaire for patients with vertebral fractures. This questionnaire, QUALEFFO, includes questions in the domains pain, physical function, social function, general health perception and mental function. QUALEFFO was validated in a multicenter study in seven countries. The study was done in 159 patients aged 55-80 years with clinical osteoporosis, i.e., back pain and other complaints with at least one vertebral fracture and lumbar bone mineral density T-score <-1. Patients with a recent vertebral fracture were excluded because of unstable disease. Controls were age- and sex-matched, and did not have chronic back pain or vertebral fractures. Subjects with conditions exerting a major influence on quality of life were excluded. The QUALEFFO was administered twice within 4 weeks and compared with a generic questionnaire, the Short Form 36 of the Medical Outcomes Study (SF-36). Standard spinal radiographs were made for assessment of vertebral height. Seven questions were removed from the analysis because of low response rate, linguistic ambiguities or redundancy. The 41 remaining questions were analyzed for repeatability, internal consistency and the capacity to discriminate between patients with vertebral fractures and controls. Comparison with the SF-36 was performed within similar domains by conditional logistic regression and by receiver operating characteristic (ROC) curves. The repeatability of QUALEFFO was good (kappa statistics 0.54-0.90) and 26 of 41 questions had a kappa score >/=0.70. The internal consistency of the five domains was adequate, with Crohnbach alpha around 0.80. All except five questions discriminated significantly between patients and controls. The median scores of QUALEFFO were significantly higher in patients with vertebral fractures than in controls in all five domain (p<0. 001), which is consistent with decreased quality of life in patients with osteoporosis. Spinal radiographs were assessed using the McCloskey-Kanis algorithm. According to this, 124 patients (78%) had vertebral fractures of >/=3 SD severity, in contrast with 7 controls (4%). Significant correlations existed between scores of similar domains of QUALEFFO and the SF-36, especially for pain, physical function and mental function. All five domains within each questionnaire discriminated significantly between fracture cases and controls. The odds ratios for pain and social function were greater for QUALEFFO, while general health perception was more discriminating using the SF-36. The ROC curve analysis of QUALEFFO indicated that all five domains were significantly predictive of vertebral fractures. When comparing similar domains of the two questionnaires, QUALEFFO domains demonstrated significantly better performance for pain, physical function and social function. The QUALEFFO total score and SF-36 physical composite score showed similar performance. In conclusion, QUALEFFO is repeatable, coherent and discriminates well between patients with vertebral fractures and control subjects. The results of this study confirm the decreased quality of life in patients with vertebral fractures.